Pengaruh Harga dan Rasa terhadap Preferensi Konsumen Teh Kulit Buah Naga di Kabupaten Banyuwangi - Annisa Amalia Putri; Nanda Rusti; Kurniawan Muhammad Nur (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Banyuwangi district has a high productivity of dragon fruit and is a superior horticultural agricultural commodity. One of the areas in Banyuwangi district that has great potential in cultivating dragon fruit is Jambewangi Village. A rich harvest will cause a surplus of dragon fruit on the market, lowering the sale price. During this time, the dragon fruit was eaten, and only the meat was processed, while the fruit's skin was not optimally utilized. The researchers wanted to create an innovation such as a product of herbal tea leather fruit. The research aimed to know and analyze consumers' preferences for the new product of Jambewangi village. This research was conducted from June until September 2023. The variables used in this study are price and taste. The research uses a quantitative approach by using a 1-5 Likert scale questionnaire in the tourist and culinary areas of Banyuwangi District. The sampling approach used is simple random sampling. The data is 32 culinary tourists. The data obtained will be analyzed through validity tests, reliability tests, classical assumption tests, and linear regression tests. The results of this study showed that there is a significant influence between price and taste on consumer preferences, with the F value counting of 16,784 > F table 3.30, so it is understood that when price variables and taste increase together, then the variable of consumers preference also increases, on the contrary, when the price variable and taste decreases. Consumers' preference variables also experience a decrease.